School Closures and Parental Labor Supply: Differential Effects of Anticipated and Unanticipated Closures - Sofia Schroeter; Rafael Lalive; Kalaivani Karunanethy (Institute of Labor Economics (IZA), 2024)
This paper studies the labor supply responses of parents to anticipated school closures due to school holidays and unanticipated school closures due to the COVID-19 pandemic in Switzerland. Using the variation in the timing of school holidays by region, we find that while both fathers and mothers reduce hours worked in response to school holiday closures, fathers reduce theirs much more than mothers. To identify the effects of pandemic school closures, we focus on marginal workers – those in occupations that were resilient to the pandemic labor demand shocks but had limited ability to work remotely and therefore, faced the greatest challenge in meeting increased child care needs. We find that the unanticipated pandemic school closures reduced the hours worked of parents somewhat less than for workers without children. We find almost no negative effects on mothers, while for fathers, we find that their labor supply was affected less than that of men without children. In our heterogeneity analyses, we discover that fathers of older children and/or with greater ability to work remotely were the least affected by these school closures. This suggests that parents were able to successfully accommodate the increased child care needs due to lack of in-person schooling without any negative impact on their labor supply.
Keywords: D13; J16; J22; 330; COVID-19; school closures; lockdown measures; parental labor supply; gender